THE EFFECTIVENESS OF ICT UTILIZATION ON COGNITIVE ACHIEVEMENT IN THE VOCATIONAL EDUCATION DURING THE COVID-19 OUTBREAK IN INDONESIA - Yudha Aditya Fiandra; nFn Ambiyar; M Giatman; nFn Usmeldi; Nurhasan Syah (Kwangsan: Jurnal Teknologi Pendidikan, 2021)
In the current Covid-19 transition period, it is very necessary to use innovative vocational learning models in digital models. The number of vocational learning models using ICT as the main tool during the pandemic needs to be studied further on how the model is implemented and its effectiveness. The problem that arises is that we do not know whether the use of ICT tools in vocational learning is effectively used. This study aims to empirically verify the effectiveness of ICT in vocational education learning during the Covid-19 transition period. Meta-Analysis is used as a method to conduct this research. There are 30 latest articles reviewed during the year of 2020 to 2021. All articles are classified based on the author, year of publication, the ICT device or application used, and the results of the post-test experimental and control classes. The results are obtained after the calculation using the effect size (ES) formula. The calculation results show that the learning using ICT as a tool during the Covid-19 pandemic has a high effect (1.28) on cognitive achievement in vocational education. The conclusion of this study is that ICT-assisted learning has a high level of effectiveness and is suitable for learning in the vocational field. Then, the dominant multimedia device or application used in the vocational learning in Indonesia is the computer technology network and it is the most widely used for the application of ICT in learning.